USE OF GRASS AND SPENT MUSHROOM COMPOST AS A GROWING MEDIUM OF LOCAL TOMATO (Lycopersicon esculentum Miller) SEEDLING IN THE NURSERY - Priadi, Dody; Arfani, Agus; Saskiawan, Iwan; Mulyaningsih, Enung Sri (AGRIVITA, Journal of Agricultural Science, 2016)
The objective of this study was to investigate the response of local tomato (Lycopersicon esculentum Miller) seedlings growth on media containing grass and spent mushroom compost in the nursery. The grass compost (GC) was produced by Research Center for Biotechnology-LIPI. Whereas the spent oyster mushroom (Pleurotus ostreatus) compost (OC) and spent paddy straw mushroom (Volvariella volvacea) compost (PC) were produced by Research Center for Biology-LIPI. Growing media of tomato seedling was a mixture ofÂ  top soil (TS), rice husk charcoal (HC), grass compost (GC), spent oyster mushroom compost (OC) and spent paddy straw mushroom compost (PC) in the ratio of 1:1 as follows:Â  TS+HC, TS+HC+GC, TS+HC+OC and TS+HC+PC. The experiments were arranged in Completely Randomized Design with three replications. Growth parameters observed i.e. seedling growth, dry weight production and leaf indices. Results showed that growing medium containing spent paddy straw mushroom compost was the best to improve seedlings growth in general. However, the lowest specific leaf area (SLA) and leaf area ratio (LAR) indices were obtained by the seedlings on the medium without compost. Correlation analysis showed that highest correlations were recorded for the TS+HC+OC medium. The tomato seedling growth was improved on the media containing compost in general.